PERSEPSI TERHADAP IKLIM SEKOLAH DASAR INKLUSI - Weny Sembiring (MANASA, 2013)
Nowadays, Indonesian Government released policy to take care of special children in inclusion school, but there are still some problems in inclusion practice such as school climate. Positive school climate is important thing that can result better achievement for students. This research focused on effect of inclusive program to perception of school climate. The subjects are 93 reguler students, 5 special students, 5 parents, 4 shadow teachers, 4 reguler teachers, headmaster, and board commitee. The Perception of School Climate Scale and interview are applied. The result shows that all special and reguler children have moderate level on perception of school climate in satisfaction, teacher, achievement, opportunity to achieve success, and identity dimensions. Shadow teachers, reguler teachers, headmasters, parents, and board committee have positive perception also, but there are some barriers to be resolved such as: service quality, special need children characteristic and learning method, communication, and advance in inclusion program